2006
DOI: 10.1016/j.scitotenv.2005.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Radiocaesium (137Cs) in marine mammals from Svalbard, the Barents Sea and the North Greenland Sea

Abstract: Specific activities of the anthropogenic radionuclide, 137 Cs, were determined in marine mammals from Svalbard and the Barents and North Greenland Seas. Muscle samples were collected from 12 polar bears, 15 ringed seals, 10 hooded seals, 7 bearded seals, 14 harp seals, one walrus, one white whale and one blue whale in the period 2000-2003. The mean concentrations (F SD) of 137 Cs were: 0.72 F 0.62 Bq/kg wet weight (w.w.) for polar bears; 0.49 F 0.07 Bq/kg w.w. for ringed seals; 0.25 F 0.10 Bq/kg w.w. for hood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…More recent studies reported low levels 137 Cs in marine mammals from Svalbard and North Greenland Sea collected in the period [2000][2001][2002][2003]. Mean values (±SD) were from 0.22 ± 0.11 Bq kg − 1 for bearded seals to 0.72 ± 0.62 Bq kg − 1 w.w. for polar bears (Ursus maritimus) (Andersen et al, 2006). Similar low average concentrations of 137 Cs in muscle were reported in Pacific walruses (Odobenus rosmarus divergens) (0.07 Bq kg − 1 w.w) and bearded seal (Erignathus barbatus) (0.17 Bq kg − 1 w.w.) from St. Lawrence Island, Alaska (Hamilton et al, 2008).…”
supporting
confidence: 71%
See 1 more Smart Citation
“…More recent studies reported low levels 137 Cs in marine mammals from Svalbard and North Greenland Sea collected in the period [2000][2001][2002][2003]. Mean values (±SD) were from 0.22 ± 0.11 Bq kg − 1 for bearded seals to 0.72 ± 0.62 Bq kg − 1 w.w. for polar bears (Ursus maritimus) (Andersen et al, 2006). Similar low average concentrations of 137 Cs in muscle were reported in Pacific walruses (Odobenus rosmarus divergens) (0.07 Bq kg − 1 w.w) and bearded seal (Erignathus barbatus) (0.17 Bq kg − 1 w.w.) from St. Lawrence Island, Alaska (Hamilton et al, 2008).…”
supporting
confidence: 71%
“…Thus, data are available from other regions, including the Arctic, Asian and European coastal waters, Lake Baikal and the Caspian and Black Seas. These studies reported average levels of 137 Cs that varied between 0.2 and 17 Bq kg −1 wet weight (w.w.) (Cooper et al, 2000;Yoshitome et al, 2003;Gwynn et al, 2005;Andersen et al, 2006;Malta & Carvalho, 2011). Cesium-137 levels in tissues of marine mammals have been suggested as chemical marker for radioactive pollution in the marine environment, and correlations between tissue levels and seawater levels have been reported (Yoshitome et al, 2003).…”
mentioning
confidence: 99%
“…Numerous local sources of potential radionuclide contamination are known in the region, for example, nuclear reactor dump sites and atmospheric nuclear bomb testing sites on Novaya Zemlya. It appears from the data reported by Andersen et al (2006) that these potential sources have had little impact on marine mammals in the European Arctic. In general, pollution acts across large temporal and spatial scales, potentially having negative effects on polar bear reproduction and survival in several populations.…”
Section: Radionuclide Contaminationmentioning
confidence: 99%
“…The low 137 Cs levels observed in the marine mammals studied by Andersen et al (2006) (Hallstadius et al 1982;Kershaw and Baxter 1995;Strand et al 2002). Numerous local sources of potential radionuclide contamination are known in the region, for example, nuclear reactor dump sites and atmospheric nuclear bomb testing sites on Novaya Zemlya.…”
Section: Radionuclide Contaminationmentioning
confidence: 99%
“…Different radioactivity levels of anthropogenic 137 Cs in soils, bottom sediments and living organisms have been also noted (Gwynn et al 2004;Andersen et al 2006;Stepanets et al 2007;Zaborska et al 2010). Measurements of radioactive isotopes appearing after nuclear tests in the near-bottom waters were performed intensively in the 1950s and at the beginning of the 1960s.…”
Section: Introductionmentioning
confidence: 99%